Pertumbuhan dan Karakter Anatomi Mimosa Air (Neptunia oleracea Lour.) pada Air yang Terpapar Logam Aluminium (Al) - Elvi Rusmiyanto Pancaning Wardoyo, Mutiara Nugie Septiani, Mukarlina, (Jurnal Protobiont, 2017)
Water mimosa (Neptunia oleracea Lour.) is one kind of aquatic plant which is potential to have adaptive ability to heavy metal exposure in water. Among heavy metals that can contaminate water is aluminum originated from the use of aluminum sulfate [Al2(SO4)3], commonly known as alum for water clarifying. The research ran for 2 months, from January to March 2017. The research used Completely Randomized Design which consisted of six aluminium sulfate concentration treatments: control, 50, 75, 100, 125, and 150 ppm. The research findings showed that aluminum had influence on N. oleracea morphologically, which was marked by the leaves becoming yellowish and the roots becoming softer. Anatomically, seen from the slide of the root, the treatment using the highest concentration resulted in a shrinkage of stele area up to 69,43%. In the slide of the plant stem, the aerenchyma was more distantly spread, and from the slide of the leaf there was a color change of the tissue to be brown. Nevertheless, N. oleracea still could survive in water with aluminum concentration of 150 ppm.